2006
DOI: 10.1109/tnsre.2006.870497
|View full text |Cite
|
Sign up to set email alerts
|

Solutions to electromagnetic interference problems between cochlear implants and GSM phones

Abstract: For persons using cochlear implants, electromagnetic compatibility (EMC) problems may sometimes be an obstacle to using digital cellular telephones. This study aimed at exploring the benefit of three new assistive listening device prototypes that eliminate or diminish EMC problems. Ten experienced cochlear implant users listened in quiet to running speech samples and a sentence test on a landline phone, a digital cellular phone with and without three prototypes. The subjects' performance was assessed using a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…More recently, Qian et al developed a mobile telephone adapter based on wireless Bluetooth technology and tested it with three Med-El implant recipients [10]. Patients reported that the [16]. They concluded that the prototypes can help telephonic communication, although further development is needed.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Qian et al developed a mobile telephone adapter based on wireless Bluetooth technology and tested it with three Med-El implant recipients [10]. Patients reported that the [16]. They concluded that the prototypes can help telephonic communication, although further development is needed.…”
Section: Discussionmentioning
confidence: 99%
“…The great diffusion that mobile communication systems have gained in the last decades, together with the parallel increase in the number of active implantable medical devices, have prompted the scientific community to consider the potential electromagnetic interference (EMI) between EMF and medical devices. Several studies have investigated, both in vivo and in vitro, the potential adverse effects of mobile terminals on pacemakers, implantable cardioverters, brain stimulator, cochlear implants and other similar implantable devices [2][3][4][5]. However, it is still difficult to define a standard measure protocol and the threshold levels at which the exposure to EMF can cause adverse health consequences for the implanted patient.…”
mentioning
confidence: 99%
“…In principle, RF-EMF can interfere with implants such as pacemakers or cochlear implants ( Sorri et al, 2006 ) and thus indirectly affect well-being. This interaction is well understood and avoided by proper electromagnetic compatibility testing of implants and is thus not considered in this review.…”
Section: Methodsmentioning
confidence: 99%